Experiences of Teachers and Learners Transitioning from Isixhosa to English Instruction in Grade 4 - Zano, Kufakunesu; Mgijima, Lungelwa; Mpiti, Pretty Thandiswa (Journal of Languages and Language Teaching, 2025)
The South African Language in Education Policy stipulates that African languages shall be employed as languages of learning and teaching in South African schools, at least from Grades 1 to 3. After that, there must be a switch to an additional language - in most cases, English first additional language (EFAL), as is the case with most schools in Matatiele, Alfred Nzo West District, South Africa. The topicality of this transition has led to this study, which explores the experiences of Grade 4 EFAL teachers and learners in Alfred Nzo West District transitioning from isiXhosa to EFAL as a medium of instruction in Grade 4. Data for the study was collected from participants drawn from a school in the rural Eastern Cape Province, Alfred Nzo West District. The sample comprised two Grade 4 EFAL teachers and ten learners. Qualitative data was collected through semi-structured interviews and observations while reading English texts. The findings revealed that the learners struggle to read because they were accustomed to using their home language, isiXhosa, in Grades 1-3. Now, they are using English as their Language of Teaching and Learning (LoTl), a language hardly spoken outside of the classroom. Besides, the findings showed that learners who were doing English home language in their previous schools, Grades 1-3, did not battle much with Grade 4 EFAL, since they relied on their prior linguistic knowledge accrued in these grades. To overcome Grade 4 EFAL learners’ barriers to reading, the teachers rely on parental involvement, phonics, collaborative learning and learners’ prior linguistic background. The study is important in underscoring the need to give Grade 4 EFAL learners age-appropriate reading materials because their comprehension is naturally developed as they acquire new vocabulary, and learners are cognitively engaged in less challenging texts.